Correlations between objective and self‐reported step count adherence following total knee replacement: A longitudinal repeated‐measures cohort study. (13th July 2022) - Duong, Vicky; Dennis, Simone; Ferreira, Manuela L.; Nicolson, Philippa; O'Connell, Rachel; Robbins, Sarah R.; Wang, Xia; Hunter, David J.
Abstract: Objective: To determine how physically active individuals are following total knee replacement (TKR) and how accurately they self‐report their step count adherence compared to objective measure following TKR. Methods: Observational cohort study, nested within the PATHway randomised‐clinical trial. Participants ( n  = 102) who had recently undergone TKR were recruited for the main trial. Only participant data from the intervention group were used for this study ( n  = 51). Participants in the intervention group received an activity tracker to monitor their physical activity and fortnightly health‐coaching sessions for 3 months. Adherence was objectively measured as percentage of steps completed divided by the amount prescribed by the health coach. Participants were asked to self‐report their adherence on a 1–10 numerical rating scale during health coaching sessions. Results: Data from 44 participants were available, resulting in a total of 224 paired measurements. Participant step count increased over the first 8 weeks of follow‐up, and plateaued from 8 weeks onwards at approximately 7500 steps/day. About two‐thirds (65.8%) of participants accurately self‐reported their step count adherence up until 12 weeks, the remaining one‐third (34.2%) underestimated their adherence. Paired t ‐tests demonstrated statistically significant differences between the paired measurements from weeks 2 to 10. Discussion: Participants were generally active and completed the step goal most occasions. Two‐thirds accurately self‐reported their step goal adherence. Self‐reported measures should be combined with an objective measure of adherence for greater accuracy. A further understanding of how people engage with activity trackers can be used to promote behaviour change in physiotherapy‐led interventions.